The speech act in the poem" to the student" by the poet ahmed sahnoun - Bourekoi, Noura (Milev Journal of Research and Studies, 2022)
The speech act theory is the most important thing of pragmatic lesson ,and it was founded by the English philosopher Austin and his student searl which states that every saying is an action that is accomplished, for him ,the speech act is broader than being limited to the intention of speaker ,rather ,it is related to linguistic and social custom, and in this article we will apply the theory of speech act to the poem ( to the student) by the poet Ahmed sehnoun accredited on searle’s division of the speech act.